Estimating the Hydrolysis of Glucose from Bamboo with Micro Controller PID Type Arduino UNO and Fuzzy Method - Ni Ketut Sari; Dira Ernawati; Intan Yuniar Purbasari; Basuki Rahmat (New Approaches in Engineering Research Vol. 12, 2021)
Glucose needs each year has increased significantly while glucose production has decreased, this is because supplies of the raw materials limited, where bamboo is one of the raw material alternatives to glucose. The selection of bamboo plants based on levels of cellulose which ranges from 42.4%-53.6%, bamboo plants are plants that can grow quickly and easily grown in various regions in Indonesia. The purpose of research on the hydrolysis process of bamboo using a Proportional Integral Derivative (PID) microcontroller is to digitally process hydrolysis in determining optimal temperature and glucose levels using the Fuzzy method and the Delphi programming simulation language. The production of glucose from bamboo using hydrolysis and pretreatment process, in the hydrolysis process of the microcontroller equipped PID type Arduino UNO, the application of microcontrollers PID using the Fuzzy method and simulation language Delphi programming. Research results in the form of the temperature profile, levels of cellulose hydrolysis time function, and the function time of the hydrolysis of glucose levels. At the time of the detailed set point temperature profile 97°C, at an early stage shows the result of the PID process control with fault temperature below ten°C, the temperature as measured 94,696°C, hydrolysis time 20 seconds. As time went on the hydrolysis process control, PID shows the temperature measured is 96.59°C, at 137 seconds, measured temperature shows 97°C following the temperature set point, used as a basis to design tools in the process of hydrolysis. Optimization of cellulose levels function hydrolysis time is 18.7% and the optimization of the hydrolysis time function of glucose levels is 23,6%. Process design with the production of glucose from bamboo with hydrolysis equipped microcontroller control PID temperature obtained the optimum levels of glucose.